Structural Controls on Crustal Fluid Circulation and Hot Spring Geochemistry Above a Flat‐Slab Subduction Zone, Peru. (14th July 2020) - Scott, B. E.; Newell, D. L.; Jessup, M. J.; Grambling, T. A.; Shaw, C. A.
Abstract: Hot spring geochemistry from the Cordillera Blanca and Cordillera Huayhuash, Peru, reveal the influence of crustal‐scale structures on geothermal fluid circulation in an amagmatic region located above a flat‐slab subduction zone. To test the influence of contrasting modes of faulting in these regions, springs were targeted along the Cordillera Blanca detachment fault, within its hanging wall, in the footwall of the detachment, and in the Cordillera Huayhuash. Hot springs along the Cordillera Blanca detachment fault zone are associated with recent extension and normal faulting, and those in its footwall and the Cordillera Huayhuash are located in the Marañon fold and thrust belt where compressional structures dominate. Springs along and in the hanging wall of the Cordillera Blanca detachment fault yield brackish‐saline, alkaline‐chloride waters, with oxygen, hydrogen, carbon, and chlorine stable isotope values that suggest mixing between meteoric groundwater and saline brine affected by high water‐rock interaction. Geothermometry reservoir temperature estimates (RTEs) of 91–226°C indicate maximum flow path depths of 8.7 or 11 km, depending on geothermal gradient, associated with the Cordillera Blanca detachment fault. In contrast, springs in the footwall and in the Cordillera Huayhuash exhibit a wide range of water types with an isotopic affinity to meteoric water, suggesting a greater influence from shallow groundwater and less water‐rock interaction. For these springs, RTEs of 40–98°C correspond to much shallower circulation (1.6–4 km). Results indicate that the Cordillera Blanca detachment system accommodates significantly deeper circulation of crustal fluids compared to other regional compressional structures. Key Points: The Cordillera Blanca detachment hosts a hydrothermal system and deep flow paths Hot spring aqueous and isotope geochemistry reveal crustal fluid sources, temperatures, and mixing Contrasting structural styles in the Cordillera Blanca and Cordillera Huayhuash influence water‐rock interaction and groundwater chemistry